The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/sports11080159
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Muscle Thickness and Activation during Abdominal Hollowing and Bracing in CrossFit® Athletes

Ioannis Tsartsapakis,
Georgia-Andriana Pantazi,
Agapi Konstantinidou
et al.

Abstract: Exercises that improve muscle activation are essential for maintaining spinal stability and preventing low back pain. The purpose of this study was to compare the effects of abdominal hollowing and bracing on the activation of the core muscles in CrossFit® participants using ultrasound and electromyography (EMG). Twenty-four healthy adults aged 21 to 42 years old with at least two years of CrossFit® experience performed three core stability exercises (plank, side plank, bridge) with abdominal hollowing and bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 47 publications
(106 reference statements)
2
2
0
Order By: Relevance
“…Over the past few years, there has been a debate about the most effective motor control strategy to achieve the dynamic stabilization of the core [ 40 , 53 , 54 , 55 , 56 ]. This study’s findings confirm the third hypothesis as the average relative thickness of all three core muscles (TrA, IO, LM) was greater when using the hollowing compared to the bracing maneuver ( Figure 5 ), which is consistent with previous studies [ 15 , 32 ]. Some studies have suggested that deep abdominal muscles are activated to a greater extent by abdominal hollowing, while superficial muscles are activated to a greater extent by abdominal bracing [ 26 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Over the past few years, there has been a debate about the most effective motor control strategy to achieve the dynamic stabilization of the core [ 40 , 53 , 54 , 55 , 56 ]. This study’s findings confirm the third hypothesis as the average relative thickness of all three core muscles (TrA, IO, LM) was greater when using the hollowing compared to the bracing maneuver ( Figure 5 ), which is consistent with previous studies [ 15 , 32 ]. Some studies have suggested that deep abdominal muscles are activated to a greater extent by abdominal hollowing, while superficial muscles are activated to a greater extent by abdominal bracing [ 26 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study’s findings confirm the third hypothesis as the average relative thickness of all three core muscles (TrA, IO, LM) was greater when using the hollowing compared to the bracing maneuver ( Figure 5 ), which is consistent with previous studies [ 15 , 32 ]. Some studies have suggested that deep abdominal muscles are activated to a greater extent by abdominal hollowing, while superficial muscles are activated to a greater extent by abdominal bracing [ 26 , 32 ]. Other studies, however, have reported exactly the opposite [ 14 , 27 , 57 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations